MODEL FOR PREDICTING THE QUALITY OF A RECRUIT IN THE BPO SECTOR - Vijaya Mani (Abhigyan, 2010)
This paper aims to build a predictive model that could identify a "good hire". It is based on the problem of hired candidates failing to show an expected performance and not entering the productive workforce. In this paper an effort is made to establish the validity of a performance metric. The quality of the personnel after hire and training is compared with the expected quality of this work force laid out at the outset. This is accomplished using a statistical analysis of the secondary data derived from company manuals and records. Two hundred and twenty four employees from a BPO company near Chennai constituted the test sample. This sample was analyzed using method of discriminant analysis. Using this method the candidates were classified in to two groups, viz., successful or unsuccessful and into the values of a categorical dependent, usually a dichotomy. The data on candidates whose training result is known was then used to build a predictive discriminant equation. Based on the above analysis, a predictive model was developed to classify a candidate as a good or bad hire. Thus this model can be used to track the hire quality.